Changes in the modal domain in different varieties of English as potential effects of democratization. (May 2020) - Kranich, Svenja; Hampel, Elisabeth; Bruns, Hanna
Abstract: One well-investigated recent change in English that has been linked to democratization is the ongoing change in the modal domain, which is characterized by a decline of some of the core modals (such as may, might, must ) and a rise of the so-called semi-modals (such as be able to, have to, have got to ) (cf. Leech, 2003; Mair and Leech, 2006; Leech, 2013). This process is advanced to different degrees in different varieties of English (cf. Collins, 2009a/b). Although a correlation between a society's decreasing attention to social hierarchies and changes in the use of markers of modality is intuitively convincing, there is still a lack of empirical studies linking the two phenomena. The present paper represents a first step to fill this gap by combining corpus-based and variational pragmatic methodology. Focusing on three varieties of English (British, American and Indian English), we first investigate the frequency differences in the use of the core modals in GloWbE (Corpus of Global Web-Based English). This traditional corpus-linguistic approach is supplemented by the use of discourse completion tasks (DCTs) to collect instances of requests, a speech act in which deontic modals are likely to be used. By collecting data in the respective varieties from 172 speakers belonging to a younger and an older group, we can analyze synchronic variation as well as diachronic change based on apparent-time data. The results confirm previous findings on the use of modals in different varieties of English to a large extent. Furthermore, we found the core modals' different rates of decline to be mirrored broadly in their different frequencies of occurrence in the DCT. Interesting differences between the two L1 varieties and the L2 variety investigated are brought to light. Highlights: Democratization may affect modal usage. BrE, AmE and IndE differ concerning frequency of core modals in web-based language use. IndE emerges as most conservative, as it uses the declining core modals most frequently. A triangulation of corpus data with DCTs shows interesting correspondences. There is no clear–cut relation between directness and politeness.